(untitled) (Revista Española de Fisiología, 1993)
The plasma potassium levels were measured in 15 cyclists during the "Vuelta Ciclista al País Valenciano" (700 km, 6 days), both at the start and at the end of the last stage. Plasma potassium levels increased from 4.3 +/- 1.9 mmol/l (resting) to 7.3 +/- 3.2 mmol/l at the end of the stage. The increase in plasma potassium levels was related to changes in other plasma electrolyte levels and it led to electrocardiographic T wave and QRS abnormalities.